2016
DOI: 10.1080/00207454.2016.1236382
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA: a new star in neurological diseases

Abstract: Circular RNAs (circRNAs) are novel endogenous non-coding RNAs characterized by the presence of a covalent bond linking the 3' and 5' ends generated by backsplicing. In this review, we summarize a number of the latest theories regarding the biogenesis, properties and functions of circRNAs. Specifically, we focus on the advancing characteristics and functions of circRNAs in the brain and neurological diseases. CircRNAs exhibit the characteristics of species conservation, abundance and tissue/developmental-stage-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…Accordingly, it has been demonstrated that many circRNAs serve as competing endogenous RNAs to bind with microRNAs (miRNAs) and inhibit the activity and function of the targeted miRNAs [8,9]. With the increasing number of studies on circRNAs, circRNAs have been shown to be involved in the development of several types of diseases, including cancer [10], cardiovascular disease [11], and neurological disorders [12]. Unlike linear RNA, circRNAs have a special circular covalently bonded structure, which facilitates their higher stability and resistance to RNA exonucleases [13].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, it has been demonstrated that many circRNAs serve as competing endogenous RNAs to bind with microRNAs (miRNAs) and inhibit the activity and function of the targeted miRNAs [8,9]. With the increasing number of studies on circRNAs, circRNAs have been shown to be involved in the development of several types of diseases, including cancer [10], cardiovascular disease [11], and neurological disorders [12]. Unlike linear RNA, circRNAs have a special circular covalently bonded structure, which facilitates their higher stability and resistance to RNA exonucleases [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that other kinds of ncRNAs, such as miRNAs play an essential role in the process of CNS development and diseases ( Hill and Lukiw, 2016 ; Persengiev et al, 2011 ; Yin et al, 2015 ). CircRNAs can serve as competing endogenous sponges to miRNAs and therefore by regulating their activities, circRNAs can have notable influence upon the development and diseases of the CNS ( Taulli et al, 2013 ; Lu and Xu, 2016 ; Li et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the progression of circRNA research, many researches have reported the participation of circRNAs in the progression of various diseases, including arteriosclerosis (Burd et al, 2010), nervous system disorders (Li et al, 2017b;Akhter, 2018), aging (Westholm et al, 2014), heart failure (Wang et al, 2016), and cancers (Qu et al, 2017;Zhang et al, 2018). Yet, its effect and mechanism in osteogenic differentiation requires more exploration.…”
Section: Discussionmentioning
confidence: 99%